The Economics of Precision: Comparing Attribute and Activity-Based Costing for Strategic Gain - Kurniawan, Bayu; Suryantara, Adhitya Bayu (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to compare the effectiveness of Attribute Based Costing (ABC II) and Activity-Based Costing (ABC) methods in increasing the competitive advantage of Coffee Shop. A qualitative case study was conducted on three featured menus (Marine Ford, Alabasta, and So So Beer) at a Coffee Shop in Mataram. Data were collected through interviews, observations, and analysis of financial documents. The ABC method allocates costs based on production activities, including raw material, labor, and overhead costs, while ABC II focuses on product attributes to calculate raw material costs. The results show that ABC produces more accurate cost information with an average profit margin of IDR6,238.61 per product, while ABC II reduces raw material costs by 13-15%, resulting in an average profit margin of IDR15,348.94. However, ABC II does not take into account labor and overhead costs, making it less comprehensive. The combination of the two methods can improve the efficiency of raw material costs (ABC II) without neglecting the accuracy of comprehensive costs (ABC). This study concludes that ABC is more suitable for competitive pricing strategies, while the integration of ABC II within the ABC framework has the potential to optimize cost management. The implication of the study recommends the hybrid use of both methods to increase the profitability of coffee shops in a competitive market.